The dynamic analysis of flexible riser systems - Ryan, M. S. (Cranfield University, 1988)
The aim of this thesis is to provide a design tool for the engineering analysis of the dynamics of a flexible riser system. The design tool is piovided in the form of a computer program. The two main requirements of such a program are that it is realistic and practical to use. The necessary theory is developed to allow these requirements to be satisfied. To ensure accuracy checks are made against model tests and known analytical solutions. How the computer program may be used is shown by analysing a particular riser configuration.